2017
DOI: 10.1007/s10689-017-9991-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population

Abstract: Urothelial bladder carcinoma (UBC) is the most common among urinary bladder neoplasms. We carried out a preliminary study to determine the genetic etiology of UBC in Pakistani population, for this 25 sequence variants from 17 candidate genes were studied in 400 individuals by using polymerase chain reaction-based techniques. Multivariate logistic regression analysis was performed for association analysis of the overall data as well as the data stratified by smoking status, tumor grade and tumor stage. Variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In total, 44 independent case–control studies with 35,936 subjects (13,711 cases and 22,225 controls) were included. Among them, 20 were Caucasians [15,16,20–23,34,36,37,39–43,45–48], 14 were Asians [9,11–14,17,24,26,33,44], 1 was African [38], and 9 were mixed populations [18,19,25,35]. Twenty-two case–control studies were designed as hospital-based investigation [9,11–14,17,18,21,22,24,26,33,34,38,44,46,48], seventeen studies were designed as population-based investigation [16,19,25,35–37,40,41,43,45,47], and the source of control in other five studies were unknown [15,20,23,39,42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 44 independent case–control studies with 35,936 subjects (13,711 cases and 22,225 controls) were included. Among them, 20 were Caucasians [15,16,20–23,34,36,37,39–43,45–48], 14 were Asians [9,11–14,17,24,26,33,44], 1 was African [38], and 9 were mixed populations [18,19,25,35]. Twenty-two case–control studies were designed as hospital-based investigation [9,11–14,17,18,21,22,24,26,33,34,38,44,46,48], seventeen studies were designed as population-based investigation [16,19,25,35–37,40,41,43,45,47], and the source of control in other five studies were unknown [15,20,23,39,42].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 20 were Caucasians [15,16,20–23,34,36,37,39–43,45–48], 14 were Asians [9,11–14,17,24,26,33,44], 1 was African [38], and 9 were mixed populations [18,19,25,35]. Twenty-two case–control studies were designed as hospital-based investigation [9,11–14,17,18,21,22,24,26,33,34,38,44,46,48], seventeen studies were designed as population-based investigation [16,19,25,35–37,40,41,43,45,47], and the source of control in other five studies were unknown [15,20,23,39,42]. Of all the eligible studies, 24 focused on breast cancer [12,14,15,19,20,22,33,35,36,38,41,42,44,47,48], 4 focused on esophageal cancer [13,40], 4 focused on colorectal cancer [34,37,39,46], 3 focused on hepatocellular carcinoma [9,11,26], 2 focused on non-Hodgkin’s lymphoma [43,45], 3 focused on oral and oropharyngeal cancer [18,21,25], 2 focused on renal cell carcinoma [17,24], and 2 focused on other cancers [16,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 19 were conducted in Caucasians,2644 eight performed in Asians,21,4550,54 and four were in mixed populations 5153. Nine were population-based,27,28,30,33,37,38,43,44,50 and 22 case–control were hospital-based studies 21,26,29,31,32,3436,39–42,4549,51–54. Of all the eligible studies, 11 focused on breast cancer,33,3740,44,48,49,51,53 four focused on colorectal cancer (CRC),31,32,41,52 three focused on prostate cancer (PC),26,30,34 and 13 focused on other cancers 21,27–29,35,36,42,43,4547,50,54.…”
Section: Resultsmentioning
confidence: 99%
“…Low-grade UBC definitions were as follows: G1, 18,54,62,70 G2, 35,58,62,70 G1 + G2, 36 low-grade, 69,71 and G1 + G2 + papilloma. 32 High-grade UBC was usually defined as grade 3 UBC, 11,27,29,32,36,37,47,50,67,70,72-75 a combination of G2 and G3 NMIBC, 54,66 and some studies have reported estimates for grade 4 tumors, without a reference for the grading system used (G3 + G4 42 and G2 + G3 + G4) 33 (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 99%